2012
DOI: 10.1073/pnas.1213159109
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide reduction to methane and coupling with acetylene to form propylene catalyzed by remodeled nitrogenase

Abstract: A doubly substituted form of the nitrogenase MoFe protein (α-70 Val→Ala , α-195 His→Gln ) has the capacity to catalyze the reduction of carbon dioxide (CO 2 ) to yield methane (CH 4 ). Under optimized conditions, 1 nmol of the substituted MoFe protein catalyzes the formation of 21 nmol of CH 4 within 20 min. The catalytic rate depends on the partial pressure of CO 2 (or concentration of HCO 3 − ) and the electron flux through nitrogenase. The doubly substituted MoFe protein also has the capacity to catalyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 51 publications
2
92
0
Order By: Relevance
“…A variant of the FeMo-containing nitrogenase protein, NifD, from Azotobacter vinelandii containing amino acid substitutions V70A and H195Q reduces CO 2 to CH 4 and also produces H 2 in vitro, but it is unable to reduce N 2 to NH 3 (3). Nucleotide substitutions to generate homologous substitutions of residues in R. palustris NifD (V75A and H201Q) were introduced into the nifD coding sequence by homologous recombination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variant of the FeMo-containing nitrogenase protein, NifD, from Azotobacter vinelandii containing amino acid substitutions V70A and H195Q reduces CO 2 to CH 4 and also produces H 2 in vitro, but it is unable to reduce N 2 to NH 3 (3). Nucleotide substitutions to generate homologous substitutions of residues in R. palustris NifD (V75A and H201Q) were introduced into the nifD coding sequence by homologous recombination.…”
Section: Resultsmentioning
confidence: 99%
“…Electrons derived from the oxidation of either an organic carbon source (acetate) or an inorganic compound (thiosulfate) are used to reduce CO 2 to CH 4 . HCO 3 − acquired from outside the cell is converted to intracellular CO 2 by carbonic anhydrase (11). Some CO 2 is also generated from acetate metabolism.…”
Section: Nifdmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, its ability to carry out reductive coupling of a wide variety of small alkenes, alkynes as well as N-, S-, and O-containing hydrocarbons makes this enzyme highly interesting for metabolic engineering (Seefeldt et al 2013). Yang and colleagues expanded the scope of nitrogenase reactions by introducing two amino acid substitutions in the substrate-binding pockets, conferring an ability to reduce CO 2 to methane or couple it with acetylene to form the polymer precursor propylene (Yang et al 2012). Recently, this engineered enzyme was shown to produce methane in a light-dependent manner upon expression in the purple non-sulfur bacterium Rhodopseudomonas palustris (Fixen et al 2016).…”
Section: Metabolic Engineering By Coupling Enzyme Activity To Photosymentioning
confidence: 99%
“…It was found that the nitrogenase MoFe protein is able to catalyze the CO2 reduction to methane (CH4) [45]. In total, 21 nmol of CH4 can be formed using 1 nmol of this enzyme under optimized conditions within 20 min.…”
Section: Conversion Of Co2 To Methanementioning
confidence: 99%